Eksistensi Konsepsi Kiwa-Tengen pada Tata Ruang Umah Dadia di Desa Sukawana, Kintamani, Bangli - Dwiantari, Made Chryselia; Paramadhyaksa, I Nyoman Widya; Prajnawrdhi, Tri Anggraini (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 6 No 1 (2019): April 2019, 2019)
Sukawana Village is a village patterned in the Bali Aga culture located in the highland region of Kintamani District, Bangli Regency, Bali. The village's residential area is surrounded by hilly areas, ravines, and fields belonging to the residents. Within this village area there is a parent settlement complex that is the forerunner of the village. The settlements are in four banjar areas, namely in Munduk Lampah, Banjar Tanah Daha, Banjar Sukawana, and Banjar Desa. Each of these banjars is also composed of several umah dadia units in the form of a series of residential buildings in one natah or shared yard which is inhabited by a group of people who still have family ties. The pattern of building a house in one house unit is described as following the left lane pattern ( kiwa ) and the right lane ( tengen). This pattern is formed in such a way based on many conceptual foundations that have been passed down from generation to generation. This study aims to determine the manifestation of the implementation of the concept of kiwa-tengen known in the cultural order in the village of Sukawana. The study was focused on spatial phenomena in umah dadia by applying rationalistic research methods. Findings found that the existence and application of the kiwa-tengen conception in Sukawana Village culture is related to the observer's point of view, the dichotomic conception of hulu-teben , brotherly relations between siblings and siblings, and the existence of imaginary axes in the umah dadia . Keywords: conception, kiwa-tengen , umah dadia, Sukawana Village, hulu-teben Abstrak Desa Sukawana adalah sebuah desa bercorak kultur Bali Aga yang berlokasi di wilayah dataran tinggi Kecamatan Kintamani, Kabupaten Bangli, Bali. Wilayah permukiman desa ini dikelilingi oleh daerah perbukitan, jurang, serta area ladang milik para penduduk. Dalam wilayah desa ini terdapat suatu kompleks permukiman induk yang menjadi cikal bakal desa. Permukiman tersebut berada di empat wilayah banjar , yaitu di Banjar Munduk Lampah, Banjar Tanah Daha, Banjar Sukawana, dan Banjar Desa. Masing-masing banjar ini juga tersusun atas beberapa unit umah dadia yang berwujud sederetan bangunan rumah tinggal dalam satu natah atau pekarangan bersama yang dihuni oleh sekelompok orang yang masih mempunyai hubungan ikatan keluarga. Pola bangunan rumah dalam satu unit umah dadia digambarkan menganut pola lajur kiri ( kiwa ) dan lajur kanan ( tengen ). Pola ini terbentuk sedemikian rupa berdasarkan banyak dasar konsepsual yang sudah berlaku secara turun temurun. Penelitian ini bertujuan mengetahui gambaran wujud implementasi dari konsepsi kiwa-tengen yang dikenal dalam tatanan budaya di Desa Sukawana. Kajian yang dilakukan terfokus pada fenomena keruangan dalam umah dadia dengan menerapkan metode penelitian rasionalistik. Temuan yang didapatkan bahwa keberadaan dan penerapan konsepsi kiwa-tengen dalam kultur Desa Sukawana adalah terkait dengan sudut pandang pengamat, konsepsi dikotomik hulu-teben , serta keberadaan sumbu aksis imajiner dalam pekarangan umah dadia . Kata kunci: konsepsi, kiwa-tengen, umah dadia , Desa Sukawana, hulu-teben